Marked 'h' for human: Chimeric life and the politics of the human. Issue 2 (June 2018) - Hinterberger, Amy
Abstract Chimeric life forms constitute mergers between two or more distinct beings. This article explores the making of interspecies mammalian chimeras in biomedical research where the availability of human embryonic stem cells and induced pluripotent stem cells has opened the way to radically humanize the biology of other organisms. By showing how chimeric life forms are foundational to biology, however, I loosen the compelling grip that chimeras have as liminal and monstrous. To the story of the chimera, this article replies with another story, that of the human as it is differently enacted at the levels of cells, tissues and organisms. Drawing on fieldwork conducted at a stem cell laboratory and farm animal research institute, the paper argues that meanings of the human become elusive and unknown when intertwined with chimeric life. In conclusion, the article reflects on the transforming politics of the human in biomedical research.